2010
DOI: 10.1037/a0017814
|View full text |Cite
|
Sign up to set email alerts
|

The fearful-face advantage is modulated by task demands: Evidence from the attentional blink.

Abstract: Fearful faces receive privileged access to awareness relative to happy and nonemotional faces. We investigated whether this advantage depends on currently available attentional resources. In an attentional blink paradigm, observers detected faces presented during the attentional blink period that could depict either a fearful or a happy expression. Perceptual load of the blink-inducing target was manipulated by increasing flanker interference. For the low-load condition, fearful faces were detected more often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
6
25
2
1
Order By: Relevance
“…Over the past two decades, several studies have established that the AB effect can be observed with a wide variety of stimuli, such as symbols [3], pictures [4], faces [5] or words [6][8]. Typically, the AB occurs during a RSVP stream, but it can also be obtained with auditory [9], [10] or tactile paradigms [11].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, several studies have established that the AB effect can be observed with a wide variety of stimuli, such as symbols [3], pictures [4], faces [5] or words [6][8]. Typically, the AB occurs during a RSVP stream, but it can also be obtained with auditory [9], [10] or tactile paradigms [11].…”
Section: Introductionmentioning
confidence: 99%
“…First, we were interested whether emotional expression in angry or happy face photographs can capture attention at all when it is task-irrelevant. In fact, for fearful faces there is mixed evidence (Milders et al, 2006; Stein, Zwickel, Ritter, Kitzmantel, & Schneider, 2009), and it is suggested that when they are task-relevant, attentional capture is not automatic but can be reduced by increasing distraction (Stein, Peelen, Funk, & Seidl, 2010). In a visual search task, attentional capture by irrelevant facial expression has been established for happy, but not angry or fearful expression (Hodsoll, Viding, & Lavie, 2011).…”
mentioning
confidence: 99%
“…It has been shown that fearful face perception is prioritized in that such faces are often perceived more easily or quickly (Milders et al , 2006; Phelps et al , 2006; Yang et al , 2007; Stein et al , 2009, 2010, 2014; Amting et al , 2010; Stienen and de Gelder, 2011). Yet, it was unclear whether such prioritized perception of fearful faces was merely due to bottom-up processing of low-level physical features (Yang et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…attentional bink; Milders et al , 2006; Stein et al , 2009). Other studies have shown that fearful faces are more resistant to suppression by visual noise or dichoptic suppression (Yang et al , 2007; Amting et al , 2010; Stein et al , 2010, 2014; Stienen and de Gelder, 2011). …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation